Pengembangan Media Animasi Untuk Meningkatkan Keterampilan Menyimak Cerita Fiksi Di Sekolah Dasar - Nisa Hafidha; Dadan Djuanda; Aah Ahmad Syahid (Jurnal Pena Ilmiah, 2022)
This research used qualitative method, Design and Development models. The development design used ADDIE. This research found that the validation of animation media development by media design experts in the first round is 73% and second round is 92%. Further, the results of the validation by the material experts in the first round is 55% and the second round is 80%. Meanwhile, the user validation result in the first round is merely 85%. It means that the animation media of fiction stories are very feasible based on conversion of assessment criteria